Polymer versus cation of gel polymer electrolytes in the charge storage of asymmetric supercapacitors - Pal, Bhupender; Amina, Yasin; Ria, Kunwar; Yang, Shengyuan; M. M., Yusoff; Rajan, Jose (American Chemical Society (ACS Publications), 2019)
Gel polymer electrolytes (GPEs) are promising candidates for highly efficient flexible electrochemical energy storage devices as they reduce leakage and size of the device as well as improving versatility with varied choice of solvents, polymers, and ions. However, the electrochemical mechanisms governing supercapacitive charge storage using a varied choice of polymers and cations (PVA, PEG, PEO-based Na + and K + ) are not systematically evaluated. In this work, the role of GPEs on the charge storage mechanism of a flexible solid-state asymmetric supercapacitor fabricated using porous carbon as the cathode and SnO 2 -TiO 2 composite flower as the anode with various GPEs, viz., poly(vinyl alcohol), poly(ethylene oxide), poly(ethylene glycol)-NaOH, and KOH, is reported. The composite electrode greatly improves the ion transportation, and the GPEs provide interconnected ion transport channels. The as-fabricated porous carbon/GPE/composite electrode as a flexible asymmetric supercapacitor displays an increased specific capacitance (C S up to ∼42.3 F g -1 ) compared to aqueous electrolytes (up to ∼14.1 F g -1 ). Among the studied GPEs, the poly(ethylene oxide)-NaOH-based GPE showed higher C S than poly(vinyl alcohol)-NaOH and poly(ethylene glycol)-NaOH, as the former offered a high cation response under the charge/discharge process.